DIGITALIZATION OF ONLINE LANGUAGE PROGRAM PLANNING MANAGEMENT - Muzna Rohmatia Matdoan; Nuril Mufidah; Abdul Wahab Rosyidi (Universitas PGRI Palembang, 2024)
The Instagram platform is widely used in the digital age, especially for teaching and learning foreign languages. After the United States and Brazil, Indonesia ranks third in terms of Instagram usage activity. This study details the administration of Arabic language online courses on the Motivaarab Instagram account, including goals, objectives, and resources. Descriptive qualitative research is the research methodology employed, and data collection methods include documentation analysis, interviews, and observation. The study's findings indicate that the target audience for the online Arabic language program is beginner and intermediate speakers. The program's objective is to provide Reels for Maharah Kalam and Quizzes for Qawaid Lughah, and the target material has already been identified. The Motivationarab account on Instagram creates Reels, or quick movies, that often last no more than a minute. In this instance, Reels receives more attention than Quiz since the quiz consists of multiple choice questions about qawaid lughah.